Intellectual Capital Sebagai Pemoderasi Pengaruh Pengungkapan Corporate Social Responsibility Pada Market Value Added - Andini, Ni Putu Ema Leonita (E-Jurnal Akuntansi, 2024)
The increasing number of investors on the Indonesian Stock Exchange encourages an increase in the need for information in investor decision making. The information that investors most often need is an assessment of company performance. One measure of company performance is market value added. There are several factors that influence a company's market value added. This research aims to investigate the effect of disclosure of corporate social responsibility and intellectual capital as moderating variables on the market value added of mining and basic industrial and chemical sector companies listed on the Indonesia Stock Exchange. The total sample for this research was 134 companies. The research period was carried out in 2018-2021. Moderated regression analysis was used in research data analysis with EVIEWS 9.0 as a data processing tool. This research finds that disclosure of corporate social responsibility has a positive effect on the company's market value added. The research results also show that intellectual capital is a variable that strengthens the influence of corporate social responsibility disclosure on companies. Keywords: Corporate Social Responsibility; Intellectual Capital; Market Value Added.